Tourism development in the context of digital transformation in Vietnam: current situation and solutions - Tran Thi Kim Khanh (Journal of State Management, 2025)
Digital transformation has been instrumental in driving growth across various sectors, particularlytourism, in recent years. Thanks to the application of modern technologies, travelers can now easilyexplore and enjoy a diverse range of engaging experiences. Tourism businesses have also enhancedoperational efficiency by optimizing processes, services, and customer management. Moreover, statemanagement agencies have had the opportunity to innovate their models and management approachesand strengthen coordination with businesses in directing and guiding the implementation of tasks.This paper evaluates the tourism sector's outstanding achievements during the digital transformationprocess, identifies key challenges, and proposes several policy solutions to promote the sustainabledevelopment of this vital industry in Vietnam.